Photoexcited carrier dynamics within alloyed CdSeTe colloidal quantum dots and at the CdSeTe/TiO2 interface. Issue 7 (1st April 2021) - Wei, Huiyun; Wang, Hao; Xie, Jinye; Qiu, Peng; Yan, Ke; Guo, Peiyuan; He, Yingfeng; Song, Yimeng; Peng, Mingzeng; Zheng, Xinhe
Abstract: Alloying strategy in quantum dots (QDs) has shown great advantages in regulating photophysical properties and improving the performance of photovoltaic devices. Typically, CdSeTe alloy QD is proved to be a superior photosensitizer, and has presented great potential in constructing high-efficient quantum dot solar cells. However, systematic analysis for the carrier dynamics is still lacking. In this paper, the carrier dynamics within CdSeTe colloidal QDs and at the TiO2 /CdSeTe interface has been studied in detail by transient absorption (TA) spectroscopy and photoluminescence (PL) spectroscopy. TA results show that the gradient component of CdSeTe QDs leads to different electronic transition properties distinct from those of their parent binary components. Temperature-dependent time-resolved PL spectra for the CdSeTe/TiO2 demonstrate that PL lifetime decreases from 13.54 to 3.08 ns with increasing temperature from 10 to 300 K. Moreover, the electron transfer rate increases more quickly when temperature exceeds 250 K. In addition, it is confirmed that the crystallization characteristics of TiO2 have a significant impact on the interfacial carrier dynamics. A faster electron transfer from CdSeTe QDs to rutile TiO2 (R–TiO2 ) has been obtained than that to anatase TiO2 (5.65 × 10 8 /s vs 3.21 × 10 8 /s). Both QDs adsorption and electron transfer properties closely dependent on the crystal orientation of R–TiO2 single crystal. CdSeTe QDs attached to the (100) R–TiO2 single crystal surface achieve the fastest electron transfer rate than other R–TiO2 orientations of (111), (110) and (001).